Spectral characteristics of cotton seeds treated by a dielectric barrier discharge plasma - Xing-Quan Wang (Nature Portfolio, 2017)
Abstract Cold atmospheric plasma has recently emerged as a simple, low-cost and efficient physical method for inducing significant biological responses in seeds and plants without the use of traditional, potentially environmentally-hazardous chemicals, fungicides or hormones. While the beneficial effects of plasma treatment on seed germination, disease resistance and agricultural output have been reported, the mechanisms that underpin the observed biological responses are yet to be fully described. This study employs Fourier Transform Infrared (FTIR) spectroscopy and emission spectroscopy to capture chemical interactions between plasmas and seed surfaces with the aim to provide a more comprehensive account of plasma−seed interactions. FTIR spectroscopy of the seed surface confirms plasma-induced chemical etching of the surface. The etching facilitates permeation of water into the seed, which is confirmed by water uptake measurements. FTIR of exhaust and emission spectra of discharges show oxygen-containing species known for their ability to stimulate biochemical processes and deactivate pathogenic microorganisms. In addition, water gas, CO2, CO and molecules containing −C(CH3)3− moieties observed in FTIR spectra of the exhaust gas during plasma treatment may be partly responsible for the plasma chemical etching of seed surface through oxidizing the organic components of the seed coat.